Dileme tržnega vrednotenja nepremičnin v Sloveniji - Šubic Kovač, Maruška (Geodetski vestnik, 1998)
This paper gives a critical analysis of the situation in the field of market real-estate valuation methods in Slovenia. Certain methodological starting points are analysed, which have to be considered in designing a new market real-estate valuation methodology in Slovenia. Relevant data acquisition was analysed in particular, since it is indispensable for market real-estate valuation for taxation purposes
Keywords: dileme prehodnega obdobja; dilemma of transition period; marketing valuation; nepremičnine; real estate; Slovenija; tržno vrednotenje